The dilemma of Iranian women: From legal transformation to restriction and resistance for gender justice - Abdul Bar Mursyid (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2023)
The Iranian legal framework formally recognizes principles of equality, yet gender-differentiated laws and policies continue to constrain women’s rights, creating tension between domestic legal practices and international human rights norms. This study aims to analyze the development of Iranian women’s position, state-imposed restrictions on their rights, and women’s resistance strategies in pursuing gender justice within the post-revolutionary theocratic context. The study employs a qualitative library research approach with thematic analysis based on the six-phase framework of Braun and Clarke (2006). Source triangulation was used to strengthen the credibility of evidence derived from primary and secondary sources. The findings reveal three interconnected patterns. First, women’s position shifted from state-led emancipation during the Pahlavi era to increased restriction following the 1979 Revolution, while reformist movements continued to advocate gender equality through alternative interpretations of Islamic law. Second, state regulations concerning education, public participation, compulsory hijab, and bodily autonomy constrained women’s rights and were accompanied by sustained resistance, particularly following the death of Mahsa Amini. Third, Iranian women developed diverse resistance strategies through human rights advocacy, cross-ideological feminist coalitions, digital activism, and public mobilization. Overall, the findings indicate that women’s rights in Iran are shaped by an ongoing contestation between state authority grounded in Islamic legal interpretations and women’s demands for equality, autonomy, and citizenship. The study contributes to progressive legal perspectives by identifying spaces for negotiation, reinterpretation, and gradual reform within a restrictive legal environment, while highlighting women’s collective agency in advancing gender justice through legal advocacy, digital mobilization, and transnational solidarity.